Destruktivt ledarskap och förekomst av stress och utbrändhet hos anställda - Nilsson,Stefan; Bringeland,Jacob (2025)
The purpose of the study was to investigate whether there was a relationship between the experience of destructive leadership by the immediate manager and the experience of stress and burnout among employees. The study also investigated whether there was a relationship between active and passive destructive leadership and stress and burnout. Finally, the study aimed to investigate whether there was a relationship between any of the destructive leadership facets and stress and burnout. The study used the measurement tool Destrudo-L to estimate the experience of active and passive destructive leadership, and COPSOQ II to estimate stress and burnout. The study aims to contribute knowledge about the importance of leadership for the psychosocial work environment in Swedish workplaces. Previous research on the consequences of destructive leadership has been limited. Data collection was carried out with a digital questionnaire. It was answered partly by employees at a municipal administration in Malmö, and partly by respondents from LinkedIn and Facebook (N=136). The results of the study showed that destructive leadership is related to higher stress and burnout levels in employees. Furthermore, the study showed that active destructive leadership is related to higher stress and burnout levels and passive destructive leadership to higher burnout levels in employees. Finally, the study showed that the facet uncertain/unclear/disorganized is related to higher stress and burnout levels in employees. The results can contribute to increased knowledge about how destructive leadership can be linked to stress and burnout in employees.
Keywords: destruktivt ledarskap; stress; utbrändhet; Destrudo-L; COPSOQ II; destructive leadership; burnout